Viewpoint: Determining famine: Multi-dimensional analysis for the twenty-first century. (April 2020) - Maxwell, Daniel; Khalif, Abdullahi; Hailey, Peter; Checchi, Francesco
Highlights: Contemporary methods of famine analysis highlight the severity of current-status indicators. This had inadvertently led to a somewhat mono-dimensional view of famine. Dimensions of magnitude, duration, and geographic specificity should complement severity. A multi-dimensional view promotes a better understanding of famine dynamics. A better understanding of dynamics will promote better prediction, prevention, and mitigation. Abstract: Famine was, until recently, largely a matter of historical or theoretical interest, but the "four famines" threat of 2017 demonstrated that Somalia in 2011 was not an aberration or outlier: famine is a contemporary reality and threat. Current methods of famine analysis however tend to emphasize the severity of current-status indicators as the sole dimension of analysis. This article argues that a more multi-dimensional view is required for a full understanding of famine, including not only severity but also the magnitude of the crisis, the temporal dimension or duration, and the spatial dimension or geographic specificity of the crisis. The article draws on recent experience of famine analysis in Nigeria, South Sudan, Somalia, and Yemen to demonstrate the way in which our current analytical perspective misses critical dimensions of famine, and the consequences of this for analysis, prevention, and response. A more multi-dimensional perspective sheds new light on famine dynamics, but also highlights the importance of causal analysis in addition to classification or determination.